EFFECT OF METAL ON HEXAVALENT CHROMIUM REDUCTION BY ACENETOBACTER CALCOACITICUS - D. P. SAMANTARAY; B. B. MISHRA (The Bioscan, 2012)
Due to chromium mining, Sukinda in the district of Jajpur is the most polluted area in the world with hexavalent chromium, which is highly toxic to living organisms. The natural habitat of Sukinda is also characterized by presence of a large number of toxic and non-toxic metals affecting reduction of hexavalent chromium by the native novel microbial flora. This necessitates study on multiple metal effects on hexavalent chromium reduction by Acenetobacter calcoaciticus isolated from the mining area. It showed a broad range of tolerance to metals like Fe2+, Cu2+, Ni2+, Hg2+ and Co2+ up to concentration of 1000ppm, 900ppm, 1000ppm, 100ppm and 300ppm respectively. The bacteria was selected for parametric studies and observed to exhibit highest reduction 89.39% in a nutritive culture medium supplemented with 1ppm of Cupper at pH 8.0, temperature 30ºC for 24h. Therefore, A. calcoaceticus may be used for bioremediation of hexavalent chromium toxicity in different chro- mium contaminated sites.